2006
DOI: 10.1021/es052491z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Uncertainty in the Ecotoxicological Assessment of Solid Waste Leachates

Abstract: Environmental managers need suitable technological methods to use in optimization studies to improve management of hazardous waste. One of the challenges to achieving a reliable hazardous waste classification is the improvement of procedures used forthe ecotoxicological characterization of solid waste leachates. Indeed, this step requires data that meet levels of acceptable quality if scientifically based decisions are to be made. In this study, we illustrate how the variability associated with the successive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The conditions of mobile phase and flow rate were the same as depicted above, but the ratio of water with 1% acetic acid to methanol was 25:75 Inc., U.S.) was applied to measure the toxicity of the reaction solution before and after reaction in this study. This equipment is usually used to evaluate the toxicity of environmental samples such as wastewater samples in some literatures (5)(6)(7)(8). The method is based on ISO 11348-3 for determining the inhibition of the luminescence emitted by the S4 marine bacterium Vibrio fischeri (NRRL B-11177) that are sensitive to a wide range of toxicants (>2000).…”
Section: S2 Photochemical Reactormentioning
confidence: 99%
“…The conditions of mobile phase and flow rate were the same as depicted above, but the ratio of water with 1% acetic acid to methanol was 25:75 Inc., U.S.) was applied to measure the toxicity of the reaction solution before and after reaction in this study. This equipment is usually used to evaluate the toxicity of environmental samples such as wastewater samples in some literatures (5)(6)(7)(8). The method is based on ISO 11348-3 for determining the inhibition of the luminescence emitted by the S4 marine bacterium Vibrio fischeri (NRRL B-11177) that are sensitive to a wide range of toxicants (>2000).…”
Section: S2 Photochemical Reactormentioning
confidence: 99%
“…The sampling of representative waste samples, which are very heterogeneous with respect to element composition, size fractions etc., is particularly challenging in this regard and usually the most error-prone step in waste analysis (Ferrari et al, 2006). Additionally, it is extremely difficult to differentiate ENMs that are expected in low concentrations from NNMs and the natural background during analysis (Duester et al, 2014;Hassellov et al, 2008;Howard, 2010;Kammer et al, 2012;Tiede et al, 2008;Walser and Gottschalk, 2014).…”
Section: Key Materials Parameters and Available Analytical Methodsmentioning
confidence: 99%
“…Several studies already showed that MTE extractability is strongly influenced by the nature of the extracting agent, which can control element mobility [15,16]. Moreover, according to Dumat et al [51] or Ferrari et al [52], solid-liquid MTE transfers during chemical extractions are complex reactions involving numerous factors that can influence MTE speciation and release. Contact times chosen for chemical extractions were 24 h for water and only 2 h for CaCl 2 in accordance with the commonly used protocols: these two procedures carry complementary information but the results are not directly comparable.…”
Section: Mobility and Phytoavailability Of Mtementioning
confidence: 99%